Impact of Chronic Endometritis on Female Fertility - Carlos Alberto Llerena Gómez; Edwin Marcelo Miranda Solís; José Sixto Calvopiña del Castillo (Medisur)
Foundation: infertility is a health problem that affects both sexes with increasing incidence. Endometriosis is one of the most common gynecological conditions and one of the main causes of female infertility. Objective: determine the knowledge about chronic endometritis that women in the canton of Ambato, Ecuador, have. Methods: a descriptive cross-sectional study was carried out in women with chronic endometritis, belonging to the canton of Ambato, during the period from July to December 2022. The sample was 30 patients selected through non-probabilistic snowball sampling. A thematic content analysis was carried out and the Fuzzy Cognitive Maps method was used. To collect the information, a semi-structured interview was carried out. Results: there was a predominance of patients between 26 and 30 years of age. 76,7 % of the patients reported not having knowledge on the subject, 86,7 % had not received formal sexual and reproductive education and 70 % had been stigmatized. 83,3 % of the women reported not periodically visiting a reproductive health professional and 76,7 % had not accessed information on the subject. 100 % of the patients considered it necessary to hold workshops, talks and carry out community interventions to raise awareness about the impact of chronic endometritis on female fertility. Conclusions: chronic endometritis was present in women of reproductive age, so it is necessary to develop health prevention strategies to minimize its incidence.